2018
DOI: 10.1126/science.aar2058
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous to homogeneous melting transition visualized with ultrafast electron diffraction

Abstract: The ultrafast laser excitation of matters leads to nonequilibrium states with complex solid-liquid phase-transition dynamics. We used electron diffraction at mega-electron volt energies to visualize the ultrafast melting of gold on the atomic scale length. For energy densities approaching the irreversible melting regime, we first observed heterogeneous melting on time scales of 100 to 1000 picoseconds, transitioning to homogeneous melting that occurs catastrophically within 10 to 20 picoseconds at higher energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
179
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(194 citation statements)
references
References 47 publications
13
179
2
Order By: Relevance
“…Homogeneous melting can be studied experimentally with special design of sample containers or energy input (Daeges et al, 1986;Mo et al, 2018). This process differs from that studied experimentally where nucleation sites, provided by sample containers and grain-grain contacts, are typically abundant.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Homogeneous melting can be studied experimentally with special design of sample containers or energy input (Daeges et al, 1986;Mo et al, 2018). This process differs from that studied experimentally where nucleation sites, provided by sample containers and grain-grain contacts, are typically abundant.…”
Section: Theorymentioning
confidence: 99%
“…The homogeneous melting point is always greater than the equilibrium melting temperature. Homogeneous melting can be studied experimentally with special design of sample containers or energy input (Daeges et al, 1986;Mo et al, 2018).…”
Section: Theorymentioning
confidence: 99%
“…In nature, melting is usually initiated heterogeneously on surfaces, and a solid material immediately transforms into a liquid that is maintained at higher than the material's melting temperature [3,4]. However, melting homogeneously occurs inside a crystal if surface melting is suppressed, which can be experimentally achieved using coating [5,6] or laser [7][8][9][10][11][12] techniques. Homogeneous melting can be defined as the phase transition from solid to liquid in the surface-and defectfree crystal, in which there is no trigger to initiate disordering except thermal fluctuations, and nucleation is equally likely to occur anywhere.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, the limit of superheating was predicted using two different parameters based on vibrational instability and elastic shear instability, the Lindemann [1] and Born criteria [2], respectively. Even though experimental observation of the initial stage of homogeneous melting remains challenging because of the random creation of a liquid nucleus and its subsequent fast growth [5][6][7][8][9][10][11][12][13], recent developments in computer simulation have enabled us to closely examine its microscopic details [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Using molecular-dynamics (MD) simulations for a Lennard-Jones fluid, a study by Jin et al observed that homogeneous melting is initiated by clusters of vibrationally destabilised particles by satisfying the Lindemann and Born criteria [16,28].…”
Section: Introductionmentioning
confidence: 99%
“…In ultrafast pump-probe experiments, the dynamics are initiated by a pump laser, then the sample is probed with an ultrashort laser pulse, electron bunch or x-ray pulse. The opportunities for ultrafast diffraction have widened due to the rapid development of sources, detectors, and instrumentation which allow for studying matter in extreme conditions [9].…”
Section: Introductionmentioning
confidence: 99%